DEFORMATION EFFECTS IN GERMANIUM CRYSTALS WITH HOLE CONDUCTIVITY - Gaidar, G.P. (Reports of the National Academy of Sciences of Ukraine, 2023)
Field dependencies of the Hall coefficient were obtained on p-Ge single crystals with resistivity r300K ≈ 16 Ohm·cm under the conditions || || [100] and || || [111] (the magnetic field is directed along [10]; is the current through the sample) at different pressures X. Fine structures of the field dependencies of the Hall coefficient associated with the anisotropy of the heavy hole band were observed at 77 K for samples of both crystallographic orientations, with the fine structure being smoothed out with increasing pressure. A distinct difference in the behavior of the Hall coefficient with pressure was observed between weak and stronger magnetic fields. Pressure dependences of resistivity and longitudinal magnetoresistance were measured at liquid nitrogen temperature on samples of both crystallographic orientations. Anisotropy of the tensoresistance and tenso-Hall effect was clearly pronounced both in the absence and presence of pressure. It was found that the main transformation of the deformed sphere of heavy holes of the initial crystal into ellipsoids occurs (in samples of both orientations) in the range of X ≤ 0.6—0.7 GPa, and in the case of a further increase in pressure, the parameters of the formed ellipsoids change relatively weakly. In samples of both crystallographic orientations, a non-zero longitudinal magnetoresistance was found, as well as its sharply pronounced anisotropy, which does not disappear up to the maximal pressures achieved in the experiment. An increasing trend in the longitudinal magnetoresistance with increasing pressure was observed under the conditions || || [100] and 77 K.